Generation and Enhancement of Mechanical Squeezing in a Hybrid Cavity Magnomechanical System. Issue 5 (20th March 2022) - Cheng, Jing; Liu, Yu‐Mu; Yi, Xuexi; Wang, Hong‐Fu
Abstract: A scheme to generate mechanical squeezing of phonon mode in a hybrid cavity magnomechanical system composed of a yttrium iron garnet sphere and two auxiliary cavities and driven by a two‐tone laser is proposed. It is found that the strong mechanical squeezing can be generated by optimizing the ratio of blue‐detuned to red‐detuned laser amplitude. However, the mechanical squeezing can not be generated when the blue‐detuned laser is not applied. Furthermore, it is found that the two auxiliary cavities suppress the effect of the counter‐rotating terms, leading to that the mechanical squeezing can break the 3 dB dB limit even when the dissipation rate of the magnon mode is much larger than the mechanical frequency. By contrast, if only one auxiliary cavity or no auxiliary cavity is coupled to magnon mode, the mechanical squeezing beyond 3 dB dB can not be achieved in a high dissipation of the magnon mode. This scheme provides an alternative way toward the practical implementation of mechanical squeezing in a hybrid cavity magnomechanical system. Abstract : A scheme to generate strong mechanical squeezing by introducing two auxiliary cavities in a cavity magnomechanical system is proposed. It is found that mechanical squeezing can break the 3 dB limit even in the high dissipation rate of the magnon mode. This work provides an alternative way toward the practical implementation of mechanical squeezing in cavity magnomechanical systems.